Ethnic Geography: Measurement and Evidence - Roland Hodler; Michele Valsecchi; Alberto Vesperoni (Center for Economic Studies and ifo Institute (CESifo), 2017)
The effects of ethnic geography, i.e., the distribution of ethnic groups across space, on economic, political and social outcomes are not well understood. We develop a novel index of ethnic segregation that takes both ethnic and spatial distances between individuals into account. Importantly, we can decompose this index into indices of spatial dispersion, generalized ethnic fractionalization, and the alignment of spatial and ethnic distances. We use maps of traditional ethnic homelands, historical population density data, and language trees to compute these four indices for more than 150 countries. We apply these indices to study the relation between historical ethnic geography and current economic, political and social outcomes. Among other things, we document that countries with higher historical alignment, i.e., countries where ethnically diverse individuals lived far apart, have higher-quality government, higher incomes and higher levels of trust.
Keywords: C43; D63; O10; Z13; 330; ethnic diversity; ethnic geography; segregation; fractionalization; quality of government; economic development; trust